The neurosyphilis is not history. A case presentation. - Erélido Hernández Valero; Julio López Arguelles (Medisur)
The syphilis is a sexual transmitted disease, caused by the pal Treponema that has had an increment with the appearance of the syndrome of acquired immunodeficiency disease starting from 1980. In 1906 this germ was observed in the human cerebrospinal fluid, in this way it opened up the neurosiphilis diagnosis. Is presented the case of a patient who began in a sudden way with a two-phase convulsive square followed by a state of coma of several days, then appeared fever, astenia, left hemiparesis. He was entered and disorientation stigmas, nape rigidity and fever emerged of up to 39oC, twelve days later He was received in neurology room where, after a series of studies, he was diagnosed with neurosyphilis.